Influence of salinity on the thermal preference of juvenile thinlip mullet, Chelon ramada. - Bass Dye; Sophie Kuijten; Ingrid Tulp; Ewout Blom; Jan Jaap Poos; Edward Schram (Journal of Experimental Marine Biology and Ecology, 2026)

Fish are more abundant in salt marsh creeks with a salinity gradient and low drainage capacity - Hannah Charan-Dixon; Loreta Cornacchia; Nino van Hees; Stella Bos; Ingrid Tulp; Britas Klemens Eriksson (Estuarine, Coastal and Shelf Science, 2025)

The small pelagic fish food landscape and its use by common terns Sterna hirundo in the Wadden Sea - Margot A. M. Maathuis; Petra Manche; Bram Couperus; Bram Parmentier; Jan Jaap Poos; Martin Poot; Hans Schekkerman; Serdar Sakinan; Ingrid Tulp (Marine Biology, 2025)
Small pelagic fish (SPF) play a vital role in marine ecosystems, transferring energy from plankton to higher trophic levels. However, SPF dynamics in shallow coastal areas are often under-studied, despite their importance as crucial prey near breeding sites of fish-eating birds such as common terns ( Sterna hirundo ). This study had two connected objectives: to map the pelagic fish food landscape in the inlets of the Dutch Wadden Sea and to describe its use by common terns. Two hydro-acoustic fish surveys were conducted in May and October 2022, while tern distribution was assessed using aerial counts and GPS tracking. Prey selection was analyzed through camera traps and DNA analysis of faeces. Herring and sprat were the predominant species in the SPF community, with sandeel also abundant in May. Smelt was most common in freshwater-influenced areas. Most fish were below 12 cm, fitting the preferred size range for common terns. SPF energy density ranged from 20.1 to 22.1 kJ/g dry weight, with sprat having the highest values. SPF biomass showed significant spatiotemporal variability across transects, inlets, and seasons. Common terns foraged frequently around the gullies, feeding mostly on herring. A significant correlation was found between fish biomass and common tern density, indicating food landscape may be a good predictor of tern distribution and vice versa. This study presents the first integrated biomass estimates of SPF in the subtidal areas of Dutch Wadden Sea for both spring and autumn, providing essential data for future energy budget models and management strategies.

Migratory Birds Advance Spring Arrival and Egg‐Laying in the Arctic, Mostly by Travelling Faster - Thomas K. Lameris; Michiel P. Boom; Rascha J. M. Nuijten; Nelleke H. Buitendijk; Götz Eichhorn; Bruno J. Ens; Klaus‐Michael Exo; Petr M. Glazov; Sveinn Are Hanssen; Philip Hunke; Henk P. van der Jeugd; Margje E. de Jong; et al. (Global Change Biology, 2025)
In the current warming climate, many organisms in seasonal environments advance their timing of reproduction to benefit from resource peaks earlier in spring. For migrants, the potential to advance reproduction may be constrained by their migration strategies, notably their ability to advance arrival at the breeding grounds. Recent studies show various changes in migration strategies, including wintering closer to the breeding grounds, earlier departure from the wintering grounds or faster travels by spending less time at stopover sites. However, whether such changes lead to earlier arrival or earlier breeding remains an open question. We studied changes in migration and reproduction timing in 12 populations of nine migratory birds, including seabirds, shorebirds, birds of prey and waterfowl breeding at Arctic sites bordering the Greenland and Barents Sea, a region undergoing rapid climate warming. The timing of migration and reproduction was derived from tracking and field data and analysed to study (1) how timing has changed in response to the changing moment of snowmelt at the breeding grounds and (2) what adjustments in migration strategies this involved. We found that in years with early snowmelt, egg‐laying in multiple populations advanced, but only two waterfowl populations also advanced arrival in the Arctic. In contrast, arrival in the Arctic generally advanced with time, even when snowmelt or egg‐laying dates did not advance. Earlier arrival with time was mostly explained by populations traveling to the Arctic faster, likely spending less time at stopover sites. Inability to forecast conditions in the Arctic may limit birds to adjust migration timing to annually varying snowmelt, but we show that several species, particularly waterfowl, are able to travel faster and advance the timing of migration over the years. The question remains whether this reflects adaptations to Arctic climate change or other factors, for example, environmental changes along the migratory route.

The function of the Wadden Sea in the life cycle of small pelagic fish - Margot A.M. Maathuis; Florian Berg; Bram Couperus; Jan Jaap Poos; Ingrid Tulp (Estuarine, Coastal and Shelf Science, 2025)

Spatio-temporal analysis of potential factors explaining fluctuations in population size of Spisula subtruncata in the Dutch North Sea - Jimmy de Fouw; Peter W. van Horssen; Johan Craeymeersch; Mardik F. Leopold; Jack Perdon; Karin Troost; Ingrid Tulp; Jetze van Zwol; Catharina J. M. Philippart (Frontiers in Marine Science, 2024)
Bivalves play a key role in coastal ecosystems by supporting food web, modifying habitats, and their economic value for fisheries. Many bivalve species are under pressure, showing large variations in population sizes and distributions, with climate change and human activities considered as important drivers. The Dutch North Sea hosts high densities of bivalve species, dominated by the cut trough shell Spisula subtruncata , with strong interannual variations and a patchy distribution. To explore the causes of this variation, data of an extensive long-term spatial benthic monitoring program (1995-2021) was analysed using a Bayesian spatio-temporal hurdle model. We considered indicators related to human activities, biological processes, climate change and habitat preference as explanatory variables for the observed long-term temporal and spatial variations. Results revealed that medium sediment grain size was key determinant of S. subtruncata occurrence and density. Increasing sea water temperatures during winter and the post-settlement phase positively affected annual population densities, while strong north-westerly winds led to lower densities. These climate change related factors had an overall positive effect on this species in the region. Human activities like shellfish dredging and sand nourishment had no measurable impact. However, shrimp and flatfish beam trawling overlapped with S. subtruncata occurrence and were negatively related to densities, suggesting higher beam trawling intensity in these areas may negatively impacts densities. Overall, the effects were stronger at medium to finer sediments where the highest densities occurred, indicating a strong habitat-dependent effect. Despite identifying multiple drivers, unexplained annual variation suggests other not included factors like predation pressure, also play a role. More detailed studies on the combined effects of climate change-driven environmental stressors and human activities are needed to fully understand the population dynamics. This knowledge is essential for developing more adequate fisheries and coastal management strategies to sustain biodiversity.

A circumpolar study unveils a positive non‐linear effect of temperature on arctic arthropod availability that may reduce the risk of warming‐induced trophic mismatch for breeding shorebirds - Aurélie Chagnon‐Lafortune; Éliane Duchesne; Pierre Legagneux; Laura McKinnon; Jeroen Reneerkens; Nicolas Casajus; Kenneth F. Abraham; Élise Bolduc; Glen S. Brown; Stephen C. Brown; H. River Gates; Olivier Gilg; et al. (Global Change Biology, 2024)
Seasonally abundant arthropods are a crucial food source for many migratory birds that breed in the Arctic. In cold environments, the growth and emergence of arthropods are particularly tied to temperature. Thus, the phenology of arthropods is anticipated to undergo a rapid change in response to a warming climate, potentially leading to a trophic mismatch between migratory insectivorous birds and their prey. Using data from 19 sites spanning a wide temperature gradient from the Subarctic to the High Arctic, we investigated the effects of temperature on the phenology and biomass of arthropods available to shorebirds during their short breeding season at high latitudes. We hypothesized that prolonged exposure to warmer summer temperatures would generate earlier peaks in arthropod biomass, as well as higher peak and seasonal biomass. Across the temperature gradient encompassed by our study sites (>10°C in average summer temperatures), we found a 3‐day shift in average peak date for every increment of 80 cumulative thawing degree‐days. Interestingly, we found a linear relationship between temperature and arthropod biomass only below temperature thresholds. Higher temperatures were associated with higher peak and seasonal biomass below 106 and 177 cumulative thawing degree‐days, respectively, between June 5 and July 15. Beyond these thresholds, no relationship was observed between temperature and arthropod biomass. Our results suggest that prolonged exposure to elevated temperatures can positively influence prey availability for some arctic birds. This positive effect could, in part, stem from changes in arthropod assemblages and may reduce the risk of trophic mismatch.

A rockling's choice: The trade-off between thermal preference and physical structure in the five bearded rockling, Ciliata mustela - Bass Dye; Ingrid Tulp; Anieke van Leeuwen; Ewout Blom; Edward Schram (Journal of Experimental Marine Biology and Ecology, 2024)

Mismatch‐induced growth reductions in a clade of Arctic‐breeding shorebirds are rarely mitigated by increasing temperatures - Thomas K. Lameris; Pavel S. Tomkovich; James A. Johnson; R. I. Guy Morrison; Ingrid Tulp; Simeon Lisovski; Lucas DeCicco; Maksim Dementyev; Robert E. Gill; Job ten Horn; Theunis Piersma; Zachary Pohlen; et al. (Global Change Biology, 2022)
In seasonal environments subject to climate change, organisms typically show phenological changes. As these changes are usually stronger in organisms at lower trophic levels than those at higher trophic levels, mismatches between consumers and their prey may occur during the consumers’ reproduction period. While in some species a trophic mismatch induces reductions in offspring growth, this is not always the case. This variation may be caused by the relative strength of the mismatch, or by mitigating factors like increased temperature‐reducing energetic costs. We investigated the response of chick growth rate to arthropod abundance and temperature for six populations of ecologically similar shorebirds breeding in the Arctic and sub‐Arctic (four subspecies of Red Knot Calidris canutus , Great Knot C . tenuirostris and Surfbird C . virgata ). In general, chicks experienced growth benefits (measured as a condition index) when hatching before the seasonal peak in arthropod abundance, and growth reductions when hatching after the peak. The moment in the season at which growth reductions occurred varied between populations, likely depending on whether food was limiting growth before or after the peak. Higher temperatures led to faster growth on average, but could only compensate for increasing trophic mismatch for the population experiencing the coldest conditions. We did not find changes in the timing of peaks in arthropod availability across the study years, possibly because our series of observations was relatively short; timing of hatching displayed no change over the years either. Our results suggest that a trend in trophic mismatches may not yet be evident; however, we show Arctic‐breeding shorebirds to be vulnerable to this phenomenon and vulnerability to depend on seasonal prey dynamics.

Behavioural responses of eel ( Anguilla anguilla ) approaching a large pumping station with trash rack using an acoustic camera (DIDSON) - Olvin Alior van Keeken; Ralf van Hal; Hendrik Volken Winter; Ingrid Tulp; Arie Benjamin Griffioen (Fisheries Management and Ecology, 2020)
European eel, Anguilla anguilla L., migrating to the sea encounter many man‐made structures that can hamper and delay migration or induce mortality. Studying small‐scale behavioural movements in front of these man‐made structures could provide insight in further mitigating adverse effects. The behaviour of eel approaching a trash rack in front of a large pumping station was investigated using a dual‐frequency identification sonar (DIDSON). Eels approaching the trash rack swam through the rack (40.5%) but also showed turning behaviour at (44.7%) or in front of the rack (14.7%). Eels approaching the rack had varying body positions, predominantly head or tail first, but also curled up into a ball or drifted sideways. After turning in front or at the trash rack, eels showed upstream and downwards swimming towards the canal bottom. The results suggest a stepwise response to potential cues, when firstly the body position is changed in such a way that secondly, later on, enhances eventual fast upstream escapement when perceived necessary. Implications for management of these behavioural observations are discussed.

Body condition of shorebirds upon arrival at their Siberian breeding grounds - Ingrid Tulp; Hans Schekkerman; Raymond H. G. Klaassen; Bruno J. Ens; G. Henk Visser (Polar Biology, 2009)

Mechanisms promoting higher growth rate in arctic than in temperate shorebirds - Hans Schekkerman; Ingrid Tulp; Theunis Piersma; G. Henk Visser (Oecologia, 2003)